Clinical outcomes of amniotic membrane loaded with 5-FU PLGA nanoparticles in experimental trabeculectomy - Fang Hu; Xiang-Yun Zeng; Zhao-Lian Xie; Lin-Lin Liu; Xiang-Yun Zeng (International Journal of Ophthalmology, 2015)
AIM: To evaluate the effect of amniotic membrane loaded with 5-fluorouracil poly (lactic-co-glycolic acid) (PLGA) nanoparticles (5-FU-NPs) in the surgical outcomes of experimental trabeculectomy in rabbits. METHODS: Thirty-two New Zealand white rabbits were randomly categorized into four groups with 8 rabbits in each group. Group 1, the control group, performed traditional trabeculectomy without adjuvant treatment. While the experimental groups performed compound trabeculectomy with different implantations including amniotic membrane (group 2), 5-FU-NPs (group 3) and amniotic membrane loaded with 5-FU-NPs (group 4). Clinical evaluations including IOP measurement and filtration bleb analysis were performed in all groups postoperatively. RESULTS: There is no significant difference of mean IOP in all groups at first 7d after surgery. While at P14, mean IOPs of experimental group 2 (9.8±2.1 mm Hg), groups 3 (8.9±2.8 mm Hg) and group 4 (7.6±2.3 mm Hg) were significantly reduced compared to control group (12.4±2.6 mm Hg; n=8, P<0.05). At P21, mean IOPs of groups 3 (11.7±3.2 mm Hg) and group 4 (9.9±1.6 mm Hg) were significantly decreased compare to control group (17.9±1.6 mm Hg) and group 2 (16.6±2.8 mm Hg; n=8, P<0.05). At P28, mean IOPs of groups 3 (13.8±3.3 mm Hg) and group 4 (10.6±2.0 mm Hg) were also significantly reduced compare to control group (19.4±2.3 mm Hg) and group 2 (18.5±2.4 mm Hg; n=8, P<0.05). Meanwhile mean IOP of group 4 is significantly decreased compared to group 3 at P28 (n=8, P<0.05). Survival analysis of functional filtration blub in all groups revealed the longest survival time in group 4 (24.9±5.1d) compared to that in group 3 (20.6±4.3d), group 2 (15.0±5.2d) and control group (10.1±5.7d). CONCLUSION: Amniotic membrane loaded with 5-Fu-NPs may function as an effective anti-scarring implant and provides improved long-term surgical outcomes for experimental trabeculectomy in rabbits.